Regulatory effect of apoptosis on morphological changes in cell mass of porcine blastocyst through supplementation of rapamycin during in vitro culture (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The study of an in vitro embryosis is crucial in genetics for breed improvement and reproduction in livestock, identifying the causes of infertility, and stem cell application. Meanwhile, the problem of nucleic acid denaturation observed during embryo development is yet to be resolved. This study was set out to analyze the nucleic acid denaturation during the development of in vitro embryos.  Materials and Methods: Using an in-vitro fertilization-embryo in porcine, the cell development and apoptosis were evaluated by adding rapamycin by concentration to the TCM-199 containing 10% FBS or 10% porcine follicle fluid (pFF). Real-time PCR, zymography, DNA fragment, Western blot, and immunofluorescence analysis were also carried out to determine the development rate of inner cell mass in the in-vitro fertilization-embryo.  Results: The findings indicated that the addition of rapamycin to the 10% pFF group during in vitro maturation led to an increase in the rates of cleavage and blastocyst development and the expression of active matrix metallopeptidase (MMP-9), while nucleic acid denaturation was suppressed. In other words, the addition of rapamycin was found to increase the expression of MMP-2 in the inner cell mass and trophoblast, while it inhibited apoptosis.  Conclusion: The addition of rapamycin influences the regulation of apoptosis and MMPs, and based on this, it is presumed to have a positive effect on blastocyst development.J. Adv. Vet. Anim. Res., 7(4): 614-620, Dec 2020http://doi.org/10.5455/javar.2020.g459